Pendidikan Karakter: Sebuah Visi Islam Rahmatan Lil Alamin - Umum Budi Karyanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Islam constitutes the perfect and universal religion for a lifetime that has the vision of guiding human beings for better life. Islam is the religion that becomes a blessing for the whole universe. It is in line with the mission of Islamic teachings, which is to protect humans from all the forms of anarchy and injustice. At the level of values, Islam completely models kindness and noble morality as well as prohibits all bad behavior, violence, or cruelty. The dream of ideal morality in Islam is to build the world, in which both Muslims and non-Muslims live in justice, peace, love, and harmony. The dream of morality becomes the responsibility of all elements of society, particularly religious figures and intellectuals to catch moral messages of religion that are able to promote harmonious understand the definition, characteristics, and mission of Islam so that they do not need to bring the name of Islam for the sake of individual, group, or political party. Likewise, there will be no more extreme views that demonstrate the name of Islam aimed at committing the actions of terrorism, in which Islam is regarded as the religion performing terrorism.